Financial Literature and Financial Inclusion During the COVID-19 Pandemic are Used to Control Behavior Through Financial Education (Case Study on Business and Management Students of STAB Negeri Sriwijaya) - Franky Okto Bernando; Desima Fitriani Purba; Sandro Varade Purba (Institute of Computer Science (IOCS), 2022)
The covid-19 pandemic-related increase in savings served as the inspiration for this study. This is integral to the importance of financial education, financial inclusion, and financial literacy in motivating people to save. With the moderating variable of financial education that took place during the COVID-19 epidemic, this study seeks to understand the impact of financial inclusion and financial literacy on saving behavior. A questionnaire was used as the primary tool for gathering data. With the help of a sampling procedure, samples of up to 100 respondents were gathered. The data was processed using SmartPLS 3.0 and examined for convergent validity, discriminant validity, composite reliability, average variance extracted (AVE), collinearity statistics (VIF), cronbach's alpha, path coefficient test, coefficient determination, and hypothesis testing using bootstrap. The study's findings indicate that financial literacy has a positive and significant impact on saving behavior, financial inclusion has no such impact, financial literacy with the moderating variable of financial education has a positive and significant impact on saving behavior, financial inclusion with the moderating variable of financial education has a positive and significant impact on saving behavior, and financial education has a positive and significant impact on saving behavior.